Pressure-Dependent Elevation of Vasoactive Intestinal Peptide Level in Chicken Choroid - Privalov, Evgeny; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Kuerten, Stefanie; Bergua, Antonio; Hohberger, Bettina (Biology, 2023)
Simple Summary Autonomic ocular control is mediated by sympathetic, parasympathetic, and primary trigeminal afferent nerve fibers. Intrinsic choroidal neurons (ICN) contribute to this complex neuronal network. Vasoactive intestinal peptide (VIP), a major transmitter of ICN, mediates choroidal vasodilation and, thus, potentially choroidal thickness and intraocular pressure (IOP). Therefore, it was the aim of the present study to investigate the choroidal VIP level (VIPchor) in the presence of an increased atmospheric pressure in a chicken model. Chicken choroidal whole mounts were exposed to ambient pressure (n = 20) and 40 mmHg (n = 20) in a PC-controlled, open chamber system for 24 and 72 h, respectively. VIPchor was significantly increased after exposure to 40 mmHg compared to exposure to ambient pressure. This increase of the VIPchor level, representing the intracellular choroidal VIP level, might argue for a retention of VIP within the neurons, consequently decreasing vasodilatation and choroid thickness. Purpose: Autonomic control is important in maintaining ocular integrity. As recent data suggested that intrinsic choroidal neurons (ICN), an intrinsic choroidal autonomic control, may regulate choroidal thickening via release of the vasodilative vasoactive intestinal peptide (VIP), it was the aim of the study to investigate the level of choroidal VIP (VIPchor) in the presence of an increased atmospheric pressure in a chicken model. Methods: Chicken choroidal whole mounts were exposed to ambient pressure (n = 20) and 40 mm Hg (n = 20) in a PC-controlled, open chamber system for 24 and 72 h, respectively. The VIP concentration was analyzed by ELISA, and the total protein concentration was measured by the BCA assay. Statistical analysis was done using an unpaired two-tailed t-test. Results: The pressurization systems enabled choroidal whole mount pressurization (40 mm Hg) with humidifying, pressure, temperature, and gas exchange. Overall, the VIPchor level concentration was significantly increased at 40 mmHg compared to the ambient pressure (30.09 +/- 7.18 pg vs. 20.69 +/- 3.24 pg; p < 0.0001). Subgroup analysis yielded a significantly increased VIPchor level at 40 mmHg compared to the ambient pressure after 24 h (28.42 +/- 6.03 pg vs. 20.76 +/- 4.06 pg; p = 0.005) and 72 h (31.77 +/- 7.82 pg vs. 20.61 +/- 2.12 pg; p = 0.002), respectively. The VIPchor elevation at 40 mm Hg ranged between 1.37- (24 h) and 1.54-fold (72 h) compared to the ambient pressure. No difference was observed between the VIPchor level at 24 h and 72 h (p > 0.05). Conclusions: The increase of the total choroidal VIP level, representing the intracellular VIP content, in the presence of an increased ambient pressure argues for a retention of VIP within the neurons, decreasing both vasodilatation and, consequently, choroid thickness. This finding might be a passive or even active function of ICN in the regulation of choroidal thickness, ocular integrity and IOP.
CRIS-Team WoS Importer:2023-05-12